SINTESIS DAN KARAKTERISASI KOMPLEKS [Fe(NH2trz)3]X2 (X=〖Br〗^-, I^-, 〖NO〗_3^-) DENGAN TEKNIK PERTUKARAN ANION - Surya Handayani (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2018)
[Fe(NH2trz)3]SO4 complex is directly synthesized from FeSO4.7H2O and 4-amino-1,2,4,-triazol (NH2trz) in water giving 71% yield. This complex is purple at room temperature showing low-spin state and diamagnetic properties. It changes to be white towards heating showing high-spin state and paramagnetic properties at high temperature. The colour changes is reversible so it can be applied as temperature sensor, molecular switch, and memory. This phenomena is called as spin crossover (SCO). Counter anion of [Fe(NH2trz)3]2+ affects transition temperature, magnetic properties, and colour changes. In this study, [Fe(NH2trz)3]X2, where X= , , and , is synthesized from FeSO4.7H2O and NH2trz ligand with addition of corresponding salts: KBr, KI, and NaNO3 before [Fe(NH2trz)3]SO4 is formed. Fe(NH2trz)3]Br2 and [Fe(NH2trz)3](NO3)2 are obtained with 14-25% yield. These complexes have similar colour and magnetic properties as [Fe(NH2trz)3]SO4, but different transition temperature. [Fe(NH2trz)3]I2 is obtained with 89% yield and have different properties from [Fe(NH2trz)3]SO4. This complex is white at room temperature showing high spin state and paramagnetic properties. It changes to be purple towards cooling and back to be white at room temperature. It is relatively less stable than other complexes synthesized in this study as it changes to be yellow when it is exposed to open air. Keywords: complex iron(II), spin crossover (SCO), anion bromide, iodide, and nitrate.